Correlated structural and lattice phonon behavioral studies on metal imparted ZnO (MxZn1-xO) multilayer interfaces. - Ibrahim, Abdul Razak

(untitled)
Undoped ZnO, Cu doped ZnO, Mg doped ZnO sol-gel was deposited on aluminium(AI) and silicone(Si) substrates followed by annealing temperatures at 350°C, 450°C and 550°C for undoped ZnO and 450°C and 550°C for Cu and Mg doped ZnO.